Privatization and Efficiency: from Principals and Agents to Political Economy - Alberto Cavaliere (Fondazione Eni Enrico Mattei (FEEM), 2006)
We survey the theoretical literature on privatization and efficiency by tracing its evolution from the applications of agency theory to recent contributions in the field of political economy. The first ones extend the theory of regulation with incomplete information to address privatization issues, comparing State Owned Entreprises (SOEs) with private regulated firms. The benefits of privatization may either derive from the constraints it places on malevolent agents or to the impossibility of commitment by a benevolent government because of incomplete contracts. Contributions dealing with political economy issues separate privatization from restructuring decisions. They either explore bargaining between managers and politicians or analyze the impact of privatization shaped by political preferences on efficiency. The theoretical results regarding the relation between privatization and efficiency do not lead to any definitive conclusion. Privatization may increase productive efficiency when restructuring takes place whereas its effects on allocative efficiency still remain uncertain.
Keywords: L33; D82; P26; 330; Regulation; Imperfect Information; Political Preferences; Privatisierung; Unvollständiger Vertrag; Wirtschaftliche Effizienz; Prinzipal-Agent-Theorie; Unvollkommene Information; Theorie der Regulierung